Inflation Targeting and Inflation Persistence in Asia - Peter Tillmann; Stefan Gerlach (Verein für Socialpolitik, 2010)
Following the Asian Financial Crisis in 1997-98, a number of regional central banks have adopted inflation targeting. We explore how successful this framework has been by looking at the persistence of inflation as measured by the sum of the coefficients in an autoregressive model for inflation using Hansen's (1999) median unbiased estimator. In contrast to non-Asian economies, we find that persistence has not declined in recent years. We hypothesise that could reflect the continued importance of the exchange rate in monetary policy in Asia or the large weight attached to food in Asian consumer prices.
Keywords: C22; E52; E31; 330